2004
DOI: 10.1097/00001756-200409150-00004
|View full text |Cite
|
Sign up to set email alerts
|

Neural correlates of the ‘Aha! reaction’

Abstract: An 'Aha! reaction' is a brief moment of exceptional thinking where an unexpected change in one's mental perspective reveals the solution to an otherwise intractable problem. In this event-related fMRI study, subjects read incomprehensible sentences followed by solution cues that were used to evoke such a reaction by triggering an alternative interpretation of the critical concepts. For 73% of the trials, subjects attributed their failure in the initial stage of sentence presentation to "having thought about it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
76
0
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 102 publications
(81 citation statements)
references
References 20 publications
3
76
0
2
Order By: Relevance
“…These results suggest that the hippocampus reflects the cog-nitive processes underlying the forming of novel association, and the activity is enhanced by the neural connections and associations with surrounding neural structures. These results fully explain the association of insight with the hippocampus [10] in some studies, but others have observed associations with the parahipp-ocampus [22,24] or temporal regions that are adjacent to the hippocampus and the parahippocampus gyrus (e.g., STG [11,15] and temporoparietal junction [21,25,29]). …”
Section: Hippocampus Superior Temporal Gyrus and Fusiform Gyrusmentioning
confidence: 53%
See 3 more Smart Citations
“…These results suggest that the hippocampus reflects the cog-nitive processes underlying the forming of novel association, and the activity is enhanced by the neural connections and associations with surrounding neural structures. These results fully explain the association of insight with the hippocampus [10] in some studies, but others have observed associations with the parahipp-ocampus [22,24] or temporal regions that are adjacent to the hippocampus and the parahippocampus gyrus (e.g., STG [11,15] and temporoparietal junction [21,25,29]). …”
Section: Hippocampus Superior Temporal Gyrus and Fusiform Gyrusmentioning
confidence: 53%
“…left middle frontal gyrus and left frontal pole [7]. Second, some studies have observed activation of the left PFC in the breaking of mental set and presentation restructuring [15].…”
Section: Prefrontal Cortex (Pfc)mentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, some researchers have maintained that solutions to problems involving insight are remembered better than those derived without insight (Luo & Niki, 2003). Analogously, in the delayed-cue condition of the Auble and Franks (1978) paradigm, subjects might develop insight when trying unsuccessfully for an extended period of time to figure out the meaning of an ambiguous sentence; the presentation of the disambiguating cue suddenly enables them to reorient their thinking in order to achieve comprehension (Luo, Niki, & Phillips, 2004).…”
Section: Discussionmentioning
confidence: 99%